Pendidikan, Lingkungan Keluarga dan Penggunaan Instagram terhadap Minat Berwirausaha Mahasiswa - Suarningsih, Ni Luh Ayu; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 31 No 2 (2021)DO - 10.24843/EJA.2021.v31.i02.p14, 2021)
This study aims to obtain empirical evidence of the effect of accounting education, entrepreneurship education, family environment and the use of Instagram on entrepreneurial interest in undergraduate accounting students of FEB Unud. The analysis technique used is multiple linear regression analysis techniques with the method of determining the sample using purposive sampling. Data collection was done by distributing questionnaires. The sample in the study were 257 respondents. The results of this study indicate that accounting education and entrepreneurship education have a positive and insignificant effect, while the family environment and use of Instagram have a significant positive effect on the interest in entrepreneurship in the undergraduate accounting study program of FEB Unud. Keywords: Education; Family Environment; Instagram; Entrepreneurial.